68Ga-NOTA-Exendin-4 PET/CT in Localization of an Occult Insulinoma and Appearance of Coexisting Esophageal Carcinoma. (April 2016) - Luo, Yaping; Li, Naishi; Kiesewetter, Dale O.; Chen, Xiaoyuan; Li, Fang
Abstract : Abstract: A 61-year-old woman with biochemically proven endogenous hyperinsulinemic hypoglycemia and negative conventional imaging underwent 68 Ga-NOTA-exendin-4 PET/CT for localization of insulinoma. Focal intense radioactivity in the tail of the pancreas was observed that was subsequently confirmed as insulinoma pathologically after surgical resection. In addition, esophageal carcinoma with lymph node and hepatic metastases was found by FDG PET/CT in the same patient. Neither the primary carcinoma nor the metastases showed increased radioactivity on 68 Ga-NOTA-exendin-4 PET/CT.